Chronically Retained Central Venous Catheter in Deceased Donor Liver Allograft - Shannon Zielsdorf; Beau Kelly; Yuri Genyk; Juliet Emamaullee (Case Reports in Transplantation)
Central venous catheters (CVC) are commonly used across multiple medical specialties and are inserted for various reasons. A known, but rare, serious complication of CVC is fracture and retention of residual catheter. Here we describe a chronically retained catheter within the inferior vena cava (IVC) that was asymptomatic and neither diagnosed nor addressed until time of deceased donor liver donation. Prior to transplantation into the recipient, the retained catheter was removed, and a venoplasty of the suprahepatic IVC, middle hepatic vein, and left hepatic vein was performed with no significant issues after transplant in the recipient. With the persistent shortage of suitable organs for transplant leading to patients dying on the waiting list, every good quality organ should be carefully considered. Thus, even though a chronically retained, fractured CVC in a deceased organ donor presents a unique challenge, it can be managed surgically and should not be considered a contraindication to organ utilization.